The quest energy, security and the remaking of the modern world - Yergin, Daniel (New York Penguin Press, 2011)
Renowned energy authority Daniel Yergin continues the riveting story begun in his Pulitzer Prize winning book, The Prize, in this gripping account of the quest for the energy the world needs -- and the power and riches that come with it. A master story teller as well as one of the world's great experts, Yergin proves that energy is truly the engine of global political and economic change, as well as central to the battle over climate change. From the jammed streets of Beijing, the shores of the Caspian Sea, and the conflicts in the Mideast, to Capitol Hill and Silicon Valley, Yergin takes us inside the decisions and choices that are shaping our future. Without understanding the realities of energy examined in The Quest, we may surrender our place at the helm of history.
Includes bibliographical references and index.
Keywords: Power resources--Political aspects